2016
DOI: 10.1063/1.4960725
|View full text |Cite
|
Sign up to set email alerts
|

Finite time blowup of solutions to the nonlinear Schrödinger equation without gauge invariance

Abstract: A lifespan estimate and a condition of the initial data for finite time blowup for the nonlinear Schrödinger equation are presented from a view point of ordinary differential equation (ODE) mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 7 publications
0
19
0
Order By: Relevance
“…The critical case p = 1 + 2 N of Proposition 2.3 has not been proved so far. The assertion of 2.3 can be regarded as a refinement of the results of Ikeda-Wakasugi [16] and Fujiwara-Ozawa [8]. It is worth noticing that the technique by Lai-Zhou [26] seems to be difficult to apply to (2.5) because they use the positivity of heat kernel for heat equations.…”
Section: Test Function Methods For the Simple Cases In Whole Spacementioning
confidence: 65%
“…The critical case p = 1 + 2 N of Proposition 2.3 has not been proved so far. The assertion of 2.3 can be regarded as a refinement of the results of Ikeda-Wakasugi [16] and Fujiwara-Ozawa [8]. It is worth noticing that the technique by Lai-Zhou [26] seems to be difficult to apply to (2.5) because they use the positivity of heat kernel for heat equations.…”
Section: Test Function Methods For the Simple Cases In Whole Spacementioning
confidence: 65%
“…Proposition follows from Lemma by using an ordinary differential equation approach introduced by the author and Ozawa . Indeed, it is shown that for some R > 0, F(t)=Imαdouble-struckRnu(t,x)x/Rn1dxCn,p,αRn1/(p1)(F(0)>0), is a super solution of an ordinary differential equation taking the form of f ′ = f p , coming from without (−Δ) 1/2 u .…”
Section: Introductionmentioning
confidence: 99%
“…In general, ϕ ≥ 0 does not imply (−Δ) s/2 ϕ ≥ 0, and therefore, (13) does not imply (9). D'Abbicco and Reissig 12 studied global nonexistence for structural damped wave equation possessing fractional derivative by generalizing (13). For the study of structural damped wave equation, (13) works well because we have nonnegative solutions(D'Abbicco and Reissig 12, lemma 1 ), which we cannot expect for (1).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations